PEMIKIRAN IBNU KHALDUN TERHADAP KEPEMIMPINAN PEREMPUAN - Husna, Asmaul; Laman, Ilham (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
This research aims to determine Ibnu Khaldun’s views on women as leaders. The problem in this research is the lack of public trust in women who want to become leaders. This is influenced by culture and religion where women are still considered unequal to men. To answer these problems, this research uses library research methods through a normative juridical approach and a Sharia method approach. The results of this research are. Ibn Khaldun stated that leadership is legally obligatory and the requirements for being a leader are having ability, capability, acting fairly, and being physically and spiritually healthy. Both men and women can become leaders as long as they fulfill the requirements because there is no statement prohibiting this.